2020
DOI: 10.1038/s41598-020-78401-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid microbial identification and colistin resistance detection via MALDI-TOF MS using a novel on-target extraction of membrane lipids

Abstract: Rapid infection diagnosis is critical to improving patient treatment and outcome. Recent studies have shown microbial lipids to be sensitive and selective biomarkers for identifying bacterial and fungal species and antimicrobial resistance. Practical procedures for microbial lipid biomarker analysis will therefore improve patient outcomes and antimicrobial stewardship. However, current lipid extraction methods require significant hands-on time and are thus not suited for direct adoption as a clinical assay for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 35 publications
(57 reference statements)
0
54
0
Order By: Relevance
“…These results suggest that lipid A molecular profiles can be used as a taxonomic index and detection marker for bacteria. In fact, research on the detection of drug-resistant and pathogenic bacteria focusing on lipid A has recently emerged [ 31 , 32 , 33 ], and it is important to determine the structural diversity of lipid A for each bacterial strain and related phenotypes. The present study will contribute to deciphering the complex and heterogeneous landscape of lipid A in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that lipid A molecular profiles can be used as a taxonomic index and detection marker for bacteria. In fact, research on the detection of drug-resistant and pathogenic bacteria focusing on lipid A has recently emerged [ 31 , 32 , 33 ], and it is important to determine the structural diversity of lipid A for each bacterial strain and related phenotypes. The present study will contribute to deciphering the complex and heterogeneous landscape of lipid A in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that colistin heteroresistance can be mediated by PhoPQ/PmrAB-dependent cationic sugar modifications to the lipid A component of lipopolysaccharide (LPS) (12)(13)(14)(15), resulting in an increased charge of the Gram-negative bacterial outer membrane and reduced susceptibility to colistin, a cationic antimicrobial peptide. Lipid A was analyzed using a new extraction method termed fast lipid analysis technique (FLAT) (16), as well as the previously used El Hamidi et al method (17), on a representative sample of 12 colistin-heteroresistant isolates from this study using matrixassisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry in the negative-ion mode (Table S5). After culture in the presence of colistin, which enriches for the resistant subpopulation, we observed an aminoarabinose (Dm/z 131 mass shift) modification to the terminal phosphate in all heteroresistant isolates evaluated, as well as an additional phosphoethanolamine (Dm/z 123 mass shift) modification in the Escherichia coli isolate analyzed (Fig.…”
mentioning
confidence: 99%
“…The patient’s urine sample was collected for further analysis using a novel rapid lipid extraction protocol that allows for diagnosis directly from clinical samples, such as blood and urine cultures, without the need for growth by MALDI-TOF MS. This method is termed fast lipid analysis technology (FLAT) [ 12 ]. Briefly, 1 µl of urine, without concentrating, was spotted on a MALDI plate and overlaid with 1 µl of buffer, consisting of 0.2 M anhydrous citric acid and 0.1 M trisodium citrate dihydrate.…”
Section: Case Presentationmentioning
confidence: 99%